TEACHERS TRAINING: PROJECTS AND EXPERIENCES IN NON-FORMAL EDUCATION - Amaral, Tatiana Platzer do; Cordeiro Bavaresco, Marcia Regina; Silva, Renan Antonio da [UNESP] (Fundacao Univ Tocantins, 2020)
The aim of this article is to analyze the proposals of projects which were developed in the Pedagogue formation process, following the obligatory nature of the practice as curriculum component (PCC) and the experiences from the non-formal education context. In the first place, the Practice as Curriculum Component was conceptualized and adopted the National Education Guidelines and Bases Act (LDB), Act No. 9.394/1996, as its main legal framework, to subsequently describe the modality of non-formal education, differentiating it from formal education. Three proposals for projects development carried out in the 2nd period of the Pedagogy Course was then submitted, as designed and directed as for the stages of preparation, method and reference support. It was found that the results experienced in nonformal education by carrying out the projects enabled theory-based practices, which points to a formation of teachers committed to the educational reality.
Keywords: Teachers Training; Practice as Curriculum Component; Non-Formal Education